Alterations in cytoskeletal and Ca2+ cycling regulators in atria lacking the obscurin Ig58/59 module - Grogan, Alyssa; Huang, Weiliang; Brong, Annie; Kane, Maureen A.; Kontrogianni-Konstantopoulos, Aikaterini (Frontiers in Cardiovascular Medicine, 2023)
Obscurin (720-870 kDa) is a giant cytoskeletal and signaling protein that possesses both structural and regulatory functions in striated muscles. Immunoglobulin domains 58/59 (Ig58/59) of obscurin have been shown to bind to a diverse set of proteins that are essential for the proper structure and function of the heart, including giant titin, novex-3, and phospholamban (PLN). Importantly, the pathophysiological significance of the Ig58/59 module has been further underscored by the discovery of several mutations within it that are linked to various forms of myopathy in humans. We previously generated a constitutive deletion mouse model, Obscn-ΔIg58/59, that expresses obscurin lacking Ig58/59, and characterized the effects of this deletion on cardiac morphology and function through aging. Our findings demonstrated that Obscn-ΔIg58/59 male animals develop severe arrhythmia, primarily manifesting as episodes of junctional escape and spontaneous loss of regular p-waves, reminiscent of human atrial fibrillation, accompanied by significant atrial enlargement that progresses in severity with aging. To comprehensively characterize the molecular alterations responsible for these pathologies, we performed proteomic and phospho-proteomic analyses in aging Obscn-ΔIg58/59 atria. Our studies revealed extensive and novel alterations in the expression and phosphorylation profile of major cytoskeletal proteins, Ca2+ regulators, and Z-disk associated protein complexes in the Obscn-ΔIg58/59 atria through aging. These studies implicate obscurin, particularly the Ig58/59 module, as an essential regulator of the Z-disk associated cytoskeleton and Ca2+ cycling in the atria and provide new molecular insights into the development of atrial fibrillation and remodeling.